Flavonoid glycosides from Antidesma ghaesembilla - Viet Cuong, Le Canh; Trang, Do Thi; Cuc, Nguyen Thi; Nhiem, Nguyen Xuan; Yen, Pham Hai; Tuan Anh, Hoang Le; Huong, Le Mai; Minh, Chau Van; Kiem, Phan Van (Vietnam Journal of Chemistry, 2015)
Four flavone glycosides were isolated from the leaves of Antidesma ghaesembilla. They were elucidated to be vitexin, orientin, isovitexin, and homoorientin by 1D- and 2D-NMR and in comparison with literature data. These compounds have been reported from the genus Antidesma for the first time.